2020
DOI: 10.1039/d0cc02852e
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and reactivity of molybdenum complexes bearing pyrrole-based PNP-type pincer ligand

Abstract: Molybdenum complexes bearing an anionic pyrrole-based PNP-type pincer ligand have been prepared and have been found to work as catalysts for the conversion of N2 into NH3 under ambient conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“… [41] Recently, the introduction of an anionic pyrrole‐based PNP ′ ligand allowed the isolation of the complex [Mo(PNP′)I 2 ] ( 258 ), which reacted with N 2 in the presence of metallic lithium at −50 °C to afford the dimeric Mo IV nitride complex [{Li(PhMe)Mo≡N(PNP′)I} 2 ] ( 259 ) (Scheme 50 b). [201] Complex 259 catalyzes the formation of NH 3 (12 equiv) in the presence of SmI 2 and ethylene glycol, via a similar mechanism than the one proposed for complex 20 . It is interesting to note that contrary to the previously reported PNP complexes, the coordination and cleavage of N 2 is reversible in this case.…”
Section: Catalytic Systemsmentioning
confidence: 86%
“… [41] Recently, the introduction of an anionic pyrrole‐based PNP ′ ligand allowed the isolation of the complex [Mo(PNP′)I 2 ] ( 258 ), which reacted with N 2 in the presence of metallic lithium at −50 °C to afford the dimeric Mo IV nitride complex [{Li(PhMe)Mo≡N(PNP′)I} 2 ] ( 259 ) (Scheme 50 b). [201] Complex 259 catalyzes the formation of NH 3 (12 equiv) in the presence of SmI 2 and ethylene glycol, via a similar mechanism than the one proposed for complex 20 . It is interesting to note that contrary to the previously reported PNP complexes, the coordination and cleavage of N 2 is reversible in this case.…”
Section: Catalytic Systemsmentioning
confidence: 86%
“…Preliminary experiments indicate that this holds true for the corresponding reactions of 3 with Me 3 SiCl and EtI, although the resulting N-functionalized products have only been observed by NMR spectroscopy so far (see Supporting Information). Nishibayashi, Schneider, Cummins and others demonstrated that NH 3 , N(SiMe 3 ) 3 , MeCN or PhCN may be generated and released from related (N-H)-, (N-SiMe 3 )-, (N-Et)-or (N-C(O)Ph)-functionalized molybdenum imido complexes, either in a catalytic (NH 3 , N(SiMe 3 ) 3 ) [5] or in a stoichiometric fashion (MeCN, PhCN). [18] In a first screening for related stoichiometric follow-up functionalization reactions, a particularly remarkable transformation was discovered when [10][OTf] was reacted with trans-2,3-epoxybutane in MeCN.…”
Section: Methodsmentioning
confidence: 99%
“…Mes 3 Mo) were developed [2] and shown to split N 2 as well, [3] while Schrock and co-workers demonstrated that this challenging transformation may also be accomplished using a POCOP-molybdenum pincer complex with a tetragonally coordinated molybdenum center. [4] Nishibayashi, [5] Schneider [6] and MØzailles [7] augmented and advanced this approach by employing different octahedral or square pyramidal PNP-, P(NH)P-and PPPmolybdenum precursors for the cleavage of N 2 , which underlines the importance of Schrocks finding in retrospective.…”
mentioning
confidence: 99%
“…In the context of a multimetallic strategy, the process of dinitrogen reduction to ammonia was made catalytic by Nishibayashi and co-authors, employing a series of binuclear complexes supported by pincer ligands [188][189][190][191][192][193][194]. Among them, the dinitrogen-bridged dimolybdenum(0)-dinitrogen complex bearing a tridentate PNP-type pincer ligand [Mo(N2)2( tBu PNP)(PMe2Ph)], is not catalytically active [196]; and (ii) protonation of mononuclear theoretical models [Mo(N2)3( tBu PNP)] is predicted to be thermodynamically unlikely [190].…”
Section: Dinitrogen Reduction: Femo-co Of Nitrogenase Vs Synthetic Fefe and Momo Complexesmentioning
confidence: 99%